THE URGENCE OF MONEY WAKF IN IMPROVING THE COMMUNITY'S ECONOMY - Endang Purwaningsih; Basrowi Basrowi (Universitas Airlangga, 2023)
The aim of this research is to describe the role of cash waqf in improving the community's economy and the country's economic growth. The method used is by literature research with a content analysis approach. The research results show that the management/cash waqf management system found is still inadequate, thus hampering the realization of cash waqf by the community. However, if cash waqf is collected, it will become a new instrument for the government to boost the economy, especially in the post-pandemic period. The managerial implication is that there is a need to educate the public about the function of cash waqf and train nazir to be able to manage waqf using technology. The realization of appropriate waqf funds will ultimately increase the level of wakif trust in transparent and accountable waqf management.